Simplifying Blood Pressure Measurements in Clinical Settings - Reischl, Uwe; Colby, Conrad (International Journal Of Community Medicine And Public Health, 2022)
Background: Upper arm sphygmomanometry is the most commonly used method to measure blood pressure in adults. However, variations in upper arm circumference and use of different cuff-sizes results in different pressure readings. When using the same cuff size, pressure readings will be higher for larger arm circumferences and lower for smaller arm circumferences. The objective of this study was to identify an adjustment factor that will allow pressure readings obtained for any combination of arm circumference and cuff size to be compared. Methods: To investigate the relationship between arm circumferences, cuff size and pressure readings, experiments were conducted using laboratory simulations and blood pressure measurements on nineteen human subjects. Power analysis identified minimum sample size. Results were analyzed using Chi-square and t-tests. The study was conducted between 2019 and 2021 in Boise, Idaho, USA. The University institutional review board approved the use of human subjects. Results: Simulations revealed a 99% linear correlation between changes in arm circumference coverage and changes in pressure readings. Human subject tests showed a 1% change in upper arm coverage by the sphygmomanometer cuff corresponded to a 1mmHg change in both systolic and diastolic pressure readings. Conclusions: The proposed adjustment factor can simplify blood pressure measurements in clinical settings by allowing healthcare providers to use only one sphygmomanometer size. It will also provide the basis for a “reference” against which blood pressure values obtained for any combination of cuff size and arm circumference can be standardized.